TEACHING READING COMPREHENSION USING JIGSAW TECHNIQUE - Cucu Sumiati; Dede Zulkaidah; Kaswan Kaswan (IKIP Siliwangi, 2019)
English is foreign language in Indonesia. In English, reading is one of skill that must be mastered by students. By mastering reading skill, it can be easier for student to comprehend the text that they read. However many students not understand how to comprehend the English text well, it caused by inapropriate technique used by the teacher in English teaching. According to the problem an appropriate technique should be applied to improve their reading comprehension. The aims of the research is to find out whether there is any improvement in the students’ reading comprehension using jigsaw technique. In this research, the writer uses pre-experimental design.The researcher takes 30 students as the sample of this research. The instrument of this research is a test uses in pre-test and post-test.The result of this research presents that the jigsaw technique is successful to improve the students’ reading comprehension. It can be sees from paired samples t-test that there is a significant difference for the pre-test score (M = 52.33 SD = 22.234) and post-test (M = 80.17 SD = 9.048), t (29) = -9.275 , p <0.05. It can be concludes that the jigsaw technique improves the students’ reading comprehension.